1999
DOI: 10.1056/nejm199905273402101
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Residual HIV-1 Replication in Patients Receiving Combination Antiretroviral Therapy

Abstract: These findings suggest that combination antiretroviral regimens suppress HIV-1 replication in some but not all patients. Given the half-life of latently infected CD4 lymphocytes of about six months, it may require many years of effective antiretroviral treatment to eliminate this reservoir of HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
517
1
6

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 761 publications
(561 citation statements)
references
References 22 publications
33
517
1
6
Order By: Relevance
“…The CD4 ϩ CD45RO ϩ HLA DR Ϫ resting memory T cell is recognized as a major HIV-1 reservoir (1)(2)(3)(4)(61)(62)(63). We found that CD16 ϩ monocytes had about half the number of HIV-1 DNA copies contained within memory T cells with this sample size (n ϭ 11), although there was no significant difference between these cell populations.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The CD4 ϩ CD45RO ϩ HLA DR Ϫ resting memory T cell is recognized as a major HIV-1 reservoir (1)(2)(3)(4)(61)(62)(63). We found that CD16 ϩ monocytes had about half the number of HIV-1 DNA copies contained within memory T cells with this sample size (n ϭ 11), although there was no significant difference between these cell populations.…”
Section: Discussionmentioning
confidence: 68%
“…However, current HAART regimens do not eradicate HIV-1 infection. This is in part attributed to the presence of anatomical and cellular sanctuary sites where HIV-1 can persist due to a combination of poor drug penetration, viral latency, and lowlevel ongoing replication (1)(2)(3).…”
mentioning
confidence: 99%
“…P ersistence of HIV-1 proviral DNA and viral RNA in PBMC after prolonged suppression of viral replication by highly active antiretroviral chemotherapy emphasizes the importance of understanding viral latency and the mechanism of viral reactivation in provirally infected cells (1,2). The lung is a particularly important target organ for HIV-1 reactivation.…”
Section: Differentiation Of Monocytes To Macrophages Switches the Mycmentioning
confidence: 99%
“…The introduction of HAART has resulted in a major reduction of virus load and in a significant decline in mortality and morbidity among HIV-infected individuals (17,18,32,49). Unfortunately, HAART is unable to eradicate HIV infection due to its limited effects on viral reservoirs carrying replicationcompetent HIV (5,7,10,35).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of HIVinfected individuals, the introduction of highly active antiretroviral therapy (HAART) induces suppression of viral replication, which is associated with at least partial reconstitution of the CD4 ϩ T-cell pool and ultimately results in a significant decline in mortality/morbidity. Unfortunately, HAART does not eradicate the infection, and in fact, after its suspension, HIV RNA rapidly rebounds to pretherapy levels, indicating the existence of refractory reservoirs (17,31,40,42,49). Cellular sources of reemerging HIV include latently infected resting CD4 ϩ T cells as well as monocytes/macrophages (M/M) and dendritic cells.…”
mentioning
confidence: 99%